Optimizing Stocking Density for Asian Seabass (Lates calcarifer Bloch, 1790) in Estuarine Floating Cages - Thomas, Sujitha; Rajesh, K. M.; Ail, Sunil Kumar; Viswambharan, Divya; Sulochanan, Bindu; Akhila, U. A.; Dharshan, K. S.; Harshitha, R.; Luhai, Abdul (Fishery Technology, 2026)
Asian seabass (Lates calcarifer) is regarded as a sought-after species suitable for coastal aquaculture. Stocking density is considered to be one of the key factors influencing fish growth, feed utilization, and overall production. The present study was conducted over a period of 180 days to evaluate the significance of stocking density on the culture of Asian seabass in floating cages in estuarine waters. Asian seabass fingerlings with a mean total length of 110.46 ± 7.26 mm and mean body weight of 16.80 ± 1.26 g were stocked in floating cages (6 m × 3 m × 2 m) with four different stocking densities viz., 25, 27, 30, and 33 fish m-3, in the Panchagangavalli estuary at Kundapura, Udupi. Growth and survival were monitored under the different stocking densities throughout the 180-day culture period. At the end of the culture period, seabass fingerlings exhibited variations in growth depending on the stocking density. At a density of 25 fish m-3, fish attained an average length of 330.50 ± 23.76 mm and a weight of 453.00 ± 115.92 g. Similarly, at stocking densities of 27, 30, and 33 fish m-3, the corresponding average lengths and weights were 329.76 ± 26.45 mm and 443.56 ± 95.11 g, 329.10 ± 18.35 mm and 441.83 ± 87.65 g, and 315.66 ± 26.16 mm and 383.33 ± 78.77 g, respectively. Growth parameters such as weight gain and specific growth rate showed significant differences with respect to the stocking density. Survival rate was relatively higher at stocking densities of 25 and 30 fish m-3, while the density of 30 fish m-3 yielded higher production. The results of the study indicate that a moderate stocking density of 30 fish m-³ was the most economically feasible, yielding the highest benefit cost ratio (1.51) and return on investment (51.15%).